BIOPHOTONICS: ACCLIMATION OF PRE-SPROUTED SUGARCANE SEEDLINGS IN PROTECTED ENVIRONMENT - Almeida Neto,Luiz A. (2019)
ABSTRACT Sugarcane is considered one of the main alternatives for biofuel production and an important product of Brazilian agriculture, so it is indispensable to adopt new techniques for its cultivation and management. Thus, the present study aimed to evaluate the effect of the quality of supplemental lighting, based on light-emitting diode (LED), on the acclimation of pre-sprouted sugarcane seedlings in a protected environment. The experimental design was completely randomized, consisting of three supplemental LED lighting systems, with light proportions of 90% red + 10% blue (R:B 90/10), 80% red + 20% blue (R:B 80/20) and 70% red + 30% blue (R:B 70/30), and a control, with natural solar radiation, with 5 replicates. Multivariate principal component analysis was used based on the matrix of correlation between all variables (meteorological, physiological and biometric). It was found that the different LED lighting systems increased the photosynthetically active radiation; however, until 20 days after planting, the seedlings were little influenced by the supplemental lighting systems. At the end of the acclimation period, the R:B 80/20 lighting system was the most associated with the growth and size of sugarcane seedlings.